(untitled) (Research, Society and Development, 2022)
Introduction: The process of transsexualization is defined as: transforming oneself to be socially accepted and avoiding the suffering generated by a body that is not inhabited. According to the German philosopher Hans Jonas, life is a unity formed by body and soul, allowing freedom of choice. Thus, there is no way to promote the concept of health without a full state of physical, mental and social well-being. Objective: to analyze the process of transsexualization involving biopsychosocial aspects. Methodology: This is an integrated literature review, with articles selected from the following databases: National Library of Medicine (PubMed MEDLINE), EbscoHost, Google Scholar, Scientific Electronic Library Online (SCIELO) and Virtual Health Library (BVS). : According to the review carried out, it was found that the most relevant aspects for the discussion of the transsexualization process are the surgical practices of sexual reassignment, in addition to the bodily changes resulting from hormone therapy and the importance of understanding the individual in their biopsychosocial aspect, verifying the difficulties faced during this transitional period. Furthermore, it is important to point out that hormone therapy can entail some risks, the most prevalent being the increase in venous thromboembolism rates. Conclusion: According to the review carried out, the transsexualization process is something that must be demystified by today’s society, with this, interventions are necessary so that there is a full experience of the transsexualization process. In addition, socio-educational measures that treat the sexuality of trans people are of paramount importance, helping to prevent STIs.